Bekerja Bersama Dengan Naposo Nauli Bulung Dalam Menanam Kembali Budaya Islami Di Desa Simangambat Dolok, Kecamatan Batang Onang, Kabupaten Padang Lawas Utara - Farhan Donganta Jaya; Ahmad Siddiq; Zul Padli Tamimi; Nada Riani; Afifah Rahmah; Fadilah Hasan; Desi Wahyuni; Ryzka Mahdani; Lutfia Iramani (Institut Teknologi dan Bisnis Semarang, 2024)
Community service has the meaning of advancing or bringing back things that have been lost from the place or location of community service itself. This becomes the basis for the strength to think about what things will be used as plans or even goals for carrying out community service. The power that has been used as material to advance the place or location of community service will of course have an impact on the culture that exists at the location or place of community service, this will become a special memory for those who have embedded and brought back things that have been lost from the location or location. place of community service. As we have understood, the basis of community service is the strength of the service group. In this case, this community service is aimed at bringing back the Islamic culture that has disappeared from Simangambat Dolok village, North Padang Lawas. Where recitation for children no longer existed and was reappeared later, Islamic culture which had never existed at all and had been made to exist, was: the celebration of the Hijriah New Year which was commemorated with a torchlight parade around the village of Simangambat Dolok, North Padang Lawas. Materials and Methods. The method used for this service is to bring up the things mentioned above which also contain the values ​​of the method which is a guide in implementing community service in Simangambat Dolok village, namely: the PAR method (Participation, Action, and Research) which in the sense of In short, it takes time to collect data or even field facts needed to carry out community service. Where the data and facts found are minimal or lacking Islamic culture in the field of literacy and culture in Simangambat Dolok village. The results of this community service are quite satisfying and significant, because literacy in the religious field, in this case the Islamic religion, has increased and many children at elementary school level have become hijaiyah literate. Of course, with the celebrations commemorating the Hijriah New Year, Islamic culture has increased quite a lot and even thickened and stuck in the minds of the people of Simangambat Dolok village, North Padang Lawas. Conclusion. Islamic culture and religious literacy (reciting the Koran) specifically for children who are also part of Islamic culture, are very necessary in increasing knowledge in Simangambat Dolok village, North Padang Lawas for the future of the children in the village. This is complete for the village of Simangambat Dolok in understanding and facing the future itself. Islamic culture is quite necessary because the basis of life is religion which is equipped with knowledge about the religion itself, which in this case is Islam.